Analisis Media Pembelajaran dalam Kurikulum 1994 dan 1999: Sebuah Studi Perbandingan - Azira, Nadia; Zahron, Hafizhah Wardah Wafiroh; Hidayatullah, Muhammad Raudlatul; Fanani, Achmad Wildan (FKIP Unirow Tuban, 2025)
This research aims to analyze the differences in learning media used in the 1994 and 1999 Curriculum, with a focus on their characteristics, strengths and weaknesses. This research uses a qualitative approach using content analysis of official curriculum documents, scientific literature and supporting sources. The research findings reveal that the 1994 Curriculum relies on conventional learning media such as textbooks and simple visual aids, which are standardized but lack interactivity. In contrast, the 1999 Curriculum introduces a student-centered approach with the use of basic multimedia and group activities that enhance student participation and critical thinking. However, the implementation of learning media in the 1999 Curriculum faces challenges such as limited access to technology and teacher readiness. This research concludes that future curriculum development must integrate the strengths of both curricula to create balanced, innovative and responsive learning media that responds to the educational needs of the 21st century.